Respuesta :
Answer:
Step-by-step explanation:
The given equation is : [tex]3x-2(x+3)=4(x-2)-7[/tex]
On solving this equation and applying the distributive property, we have
⇒[tex]3x-2x-6=4x-8-7[/tex]
⇒[tex]x-6=4x-15[/tex]
Combining the like terms like terms consisting of x are solved together and the constants are solved together,
⇒[tex]x-4x=-15+6[/tex]
⇒[tex]-3x=-9[/tex]
⇒[tex]x=3[/tex]
Answer:
3x and -2x are like terms
Step-by-step explanation:
Misha have the equation : 3x-2(x+3) = 4(x-2)-7
After applying distributive property, a(b+c) = ab+ac
3x - 2x - 6 = 4x - 8- 7 ..............(1)
Now, we need to combine the like terms, like terms are the terms having the same coefficient and combining them means to combine their coefficients.
In equation (1), 3x and -2x are like terms as it have the same coefficient x
Hence we will solve them and get (3-2)x = x
Similarly, -8 and -7 can be solved and we get -7-8 = -15
Now, the equation becomes, x-6 = 4x-15
Then, again collecting the like terms on L.H.S and R.h.s and then solving, we get
4x - x = 15-6
3x = 9
x = 3